Healthy hydration habits among young females (One Health & Risk Management, 2023)
Introduction. Water that is fit for human consumption is called drinking water. Although pure water contains no calories or organic nutrients, it is a vital element for all forms of life that we know. Water is a major component of the human body, being essential for maintaining the health of cells and facilitating many body processes. Hydration habits are established at an early age. More than half of young people do not hydrate enough, which can have significant repercussions on their physical health and their cognitive and emotional functioning. This situation highlights an important health issue that has not received attention in the past. Optimal hydration is essential for physiological processes such as circulation, metabolism, temperature regulation and toxin elimination. Excessive dehydration is associated with serious health problems, but even mild dehydration can cause problems, including headaches, irritability, poorer physical performance, and reduced cognitive functioning.Aim of the study. Assessing healthy hydration habits among young females.Material and methods. A descriptive cross-sectional survey was carried out. 97 young women between the ages of 18 and 26 participated in the study. A questionnaire was used that included 24 items with predetermined and open answers. Reference period – 2021-2022. The IBM Microsoft Excel program was used for statistical data processing.Results. Most of the young women who participated in the survey were from urban areas (88.7%). At home, at school or during activities, good hydration is important for well-being. To keep the body well hydrated and to compensate for water losses, it is essential to adopt healthy habits by drinking water regularly during the day. More than half of the young women surveyed (52.6%) have the habit of having a bottle of water when they go out. Most young women drink water between meals (91.8%) and during physical activities (89.7%). Some young women (15.5%) when they are thirsty prefer to consume other drinks instead of drinking water, for example tea, coffee, juice, compote. Most girls (96.9%) know what the recommended daily intake of drinking water is. Drinking water consumption of less than one liter per day was reported by 14.4% of young women, 1-1.5 liters – 40.2% young women, 1.5-2 liters – 34% young women, 2-2.5 liters – 5.2% and 2.5-3 liters – 6.2% young women. Adequate water consumption is beneficial to health. Inadequate hydration of the body can result in transient or chronic health problems. The most frequently reported by young women were dizziness, headache, lack of concentration, constipation, dry mouth.Conclusions. It is very important to provide the body with the necessary amount of water, to prevent and reduce the risk of illness. Educating and raising awareness of one's own health is a priority for contemporary society.
Keywords: drinking water; young women; hydration; health